Influence of Fungal Contamination on Substrate Carrying by the Leafcutter Ant Atta sexdens rubropilosa (Hymenoptera: Formicidae) - Carlos, Amanda A. [UNESP]; Forti, Luiz Carlos [UNESP]; Rodrigues, Andre [UNESP]; Verza, Sandra S. [UNESP]; Nagamoto, Nilson S. [UNESP]; Camargo, Roberto S. [UNESP] (California State University, 2009)
Toxic baits are the most used method for controlling leafcutter ants and are usually composed of a mixture of dehydrated citric pulp with an active ingredient dissolved in soy oil. In this study, we evaluate if filamentous fungi and the water content of baits influence substrate carrying by Atta sexdens rubropilosa workers. First, we determined the prevalence of fungi on formulated baits composed of different pulp sources from commercial and noncommercial toxic baits. Fungal species such as Aspergillus niger, Paecilomyces sp., and Penicillium funiculosum were found on both kinds of bait, revealing that spores of such microbes are viable after the manufacturing process. Then, the formulated bait with the highest prevalence of fungi was presented to ants in four treatments: (1) sterilized dry bait, (2) sterilized wet bait, (3) non-sterilized wet bait, and (4) non-sterilized dry bait. Overall differences in substrate carrying among treatments were observed in the first presentation (24 h) in which no signs of fungal growth were visible on baits. Specifically, treatments 3 and 4 were the most carried and were significantly different from treatments 1 and 2 that were the least carried (p = 0.0154; F = 4.71). on the second and third presentation (48 and 72 h) baits with visible fungal growth and baits overgrown with fungi were presented to ants, respectively. All treatments were carried at the same level and no significant differences were observed. Pre-selected substrates with higher moisture content and without microbes in relation to substrates with massive microbial loads were expected to produce a negative response, however, both substrates were carried. This and other aspects of substrate carrying are discussed.
Keywords: Atta; citric pulp; filamentous fungi; foraging